Code with the wisdom of the crowd : get better together with mob programming - Pearl, Mark (Pragmatic programmers., 2018)
Build systems faster and more effectively with Mob Programming. Mob Programming is an approach to developing software that radically reduces defects and key-person dependencies by having a group of people work together at a single machine. See how to avoid the most common pitfalls that teams make when first starting out. Discover what it takes to create and support a successful mob. Now you can take collaborative programming to the next level with Mob Programming.